2021
DOI: 10.1111/jan.14761
|View full text |Cite
|
Sign up to set email alerts
|

Association between illness perception and health behaviour among stroke patients: The mediation effect of coping style

Abstract: Aims This study aims to explore illness perception and coping style in relation to health behaviour and the mediating role of coping style between illness perception and health behaviour among stroke patients. Design Cross‐sectional study. Methods This survey was conducted with 515 stroke patients aged ≥18 years from September 2019 to January 2020 in Zhengzhou, China. The demographic and clinical characteristics questionnaire, Stroke Illness Perception Questionnaire‐Revised, Simplified Coping Style Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
23
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 37 publications
2
23
1
1
Order By: Relevance
“…Consistent with previous studies in China (Liu et al, 2021;Wei et al, 2021), the results of this study showed that hypertensive stroke patients' health behaviour at the end of their recovery period was at an intermediate level. In addition, the result is similar to the previous study (Bailey, Phad, McGrath, Ford, et al, 2019) showing that prevalence for each lifestyle risk behaviours (lack of regular physical activity, unhealthy diet pattern, smoking and obesity) exceeds 50% in US adults with stroke.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with previous studies in China (Liu et al, 2021;Wei et al, 2021), the results of this study showed that hypertensive stroke patients' health behaviour at the end of their recovery period was at an intermediate level. In addition, the result is similar to the previous study (Bailey, Phad, McGrath, Ford, et al, 2019) showing that prevalence for each lifestyle risk behaviours (lack of regular physical activity, unhealthy diet pattern, smoking and obesity) exceeds 50% in US adults with stroke.…”
Section: Discussionsupporting
confidence: 92%
“…Studies showed that the typical health behaviour of stroke patients in China is at a moderate or low level, requiring improvement (Liu et al, 2021; Wei et al, 2021). Studies also showed that stroke patients in other countries also have health behaviour problems such as a lack of physical activity (Wali et al, 2018), smoking and excessive drinking (Bailey, Phad, McGrath, & Haire‐Joshu, 2019), poor medication compliance (Widjaja et al, 2021) and difficulties following the recommended diet (Dearborn et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The findings of the current research confirmed our hypothesis that coping style and illness perception directly affected the QOL of Chinese adult PWE, with coping style additionally serving as a mediator of the association between QOL and illness perception. These findings remained evident even after controlling for vari-ables including age, marital status, number of antiepileptic medications, epilepsy duration, seizure frequency, and family monthly income, and represent a novel outcome among Chinese adult PWE, suggesting that illness perception and coping style represent important and modifiable variables for efforts aimed at improving QOL [25,26].…”
Section: Discussionmentioning
confidence: 97%
“…These include patient‐related factors such as physical disorders or participation restriction (Joseph et al, 2018), psychological problems (Outermans et al, 2016), factors related to caregivers’ perceptions (Gonzalez & Bakas, 2013) and relationship with family members (Gonzalez & Bakas, 2013; Hall et al, 2020), and factors related to interactions between patients and health professionals (Fitzsimons & Nicholson, 2020; Vive et al, 2020). Among these factors, individuals’ perceptions and attitudes may be the most pivotal in motivating behaviour changes (Kasten et al, 2019; Liu et al, 2021).…”
Section: Introductionmentioning
confidence: 99%